Implementation of Assessment of Learning through Project-Based Differentiated Learning in the Learning Strategy Course History Education Students FKIP UM Metro - Bobi Hidayat; Abi Krisna Arrasyid; Sowiyah Sowiyah (Foundation of Jannatun Naim Lampung, 2025)
The purpose of writing this is to describe how the implementation assessment of learning in subjects differentiated learning strategies is based on the project. The method used in this study is a qualitative descriptive method with data collection methods in the form of observation, questionnaires, and tests. The study results showed that out of 15 students who took this course, 3 students compiled projects in the form of posters, 11 students compiled projects in the form of infographics, and 1 student compiled a project in the form of a concept map. The evaluation carried out included 4 aspects, namely, planning, relevance, originality, innovation, and creativity of the projects compiled by students. The results of the planning can be said to be good because students have prepared the Canva and Flipbook applications, and students are also able to operate them well to produce interesting project creations. The relevance of the material to the project is appropriate. The original project was done by students so that its authenticity is not in doubt, and students have quite good creativity and innovation so that they produce interesting digital projects. After an assessment was carried out with the test instrument that had been prepared, the assessment was as expected. Therefore, the author recommends that educators be able to use project-based learning that is diversified with several project options both digitally and manually according to the material taught to train students' creativity and innovation.